Career Guidance to Improve Career Maturity as an Anti-Unemployment Program for College Students State University of Jakarta - R. A. Fadhallah; Lupi Yudhaningrum; Erik (Psycho Holistic, 2021)
Career maturity is needed by students to prepare themselves for the work. This can be obtained from the career guidance program during his time as a student. There are still many fresh graduate who are out of job , so career guidance is needed as an anti-unemployment program. The career guidance program is guidance in preparing for the world of work, selecting a specific job field or position / profession as well as equipping oneself to be ready to assume a position, and adjust to the various demands of the job field that is joined. This study aims to explore career guidance and career maturity as an anti-unemployment program for students of Universitas Negeri jakarta. This research is a qualitative research. Respondents in this study consist of 5 people. The results showed that career guidance must be programmed properly so the career maturity will getting better. Guidance programs focus on efforts to increase orientation towards career choices, job information and planning, consistency about preferred career choices, crystallization of job characteristics, and policies about preferred jobs.